BUILDING CHARACTERS THROUGH 3P IMPLEMNTATION (APPEARANCE-SERVICE-ACHIEVEMENT): MEMBANGUN KARAKTER MELALUI IMPLEMNTASI 3P (PENAMPILAN-LAYANAN-PENCAPAIAN) - M. Iqbal (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2020)
Character education in a micro context, centered on a holistic education unit. Education unit is the main sector that optimally utilizes and empowers all existing learning environments to initiate, improve, strengthen, and continuously enhance the character education process in educational units. Education is what will make serious efforts and always be at the forefront of efforts to form the true character of Indonesian people. Character development is divided into four pillars, namely teaching and learning activities in class, daily activities in the form of cultural development of educational units; co-curricular and / or extra-curricular activities, as well as daily activities at home and in the community. In order to realize the goals of education in schools, effective management is required, with the aim of ensuring: 1) community access to adequate education services; 2) the quality and competitiveness of education and its relevance to the needs of society; and 3) effectiveness, efficiency and accountability of education management. Appearance, service, & achievement (3P) are not new things in schools, but in fact there are still schools that do not pay attention to 3Ps properly. For example, there is still a school identity in the form of a school name board which is in a dull and rotten condition so that it cannot be read clearly & cannot provide accurate information about the school. Another example, there are still schools that ignore cleanliness, safety, comfort & beauty of the school environment such as yards, rooms (buildings) & others. Likewise, the school's lack of attention to neatness, cleanliness & harmony in the appearance and behavior shown by its residents. According to Simon Philips, character is a collection of values ​​that lead to a system, which underlies the thoughts, attitudes and behaviors that are displayed. Meanwhile, Doni Koesoema understands that character is the same as personality. Personality is considered as a characteristic, or characteristic, or style, or characteristic characteristic of a person that comes from formations received from the environment. In this sense the root of all evil and evil acts, evil acts, lies in the loss of character. Strong character is a fundamental view which gives the human population the ability to live together in peace and form a world filled with good and virtue, free from violence and immoral acts.